STUDI EKSPERIMEN KUAT LEKAT LEM PADA PASANGAN BETON RINGAN: STUDI EKSPERIMEN KUAT LEKAT LEM PADA PASANGAN BETON RINGAN - Wiguna, Edo; Mahbub, Jamal; Lestari, Nor Puji; Setiawan, Adi; Larassati, Dian Sukma (Bangun Rekaprima, 2025)
In modern construction, lightweight bricks are increasingly used as an alternative building material due to their advantages in terms of light weight, ease of installation, and energy efficiency. However, the strength of structures formed from lightweight brick masonry is highly dependent on the quality of the bond between the elements, particularly the use of adhesives such as construction glue. One crucial factor determining the bond strength is the configuration and length of the bonding surface used. This study aims to evaluate the effect of the number of bonding rows on the adhesive bond strength of lightweight brick masonry. Testing was conducted experimentally using one- and two-row bonding configurations. Each sample was subjected to compressive force through a 24.4 mm diameter cylindrical press. Results showed that the two-row configuration produced a higher bond strength, but with a larger coefficient of variation, indicating lower stability of the results. Increasing the bond length actually tended to decrease the bond strength, likely due to uneven distribution of glue and pressure. Furthermore, all test specimens fractured in the brick body, not at the bonding surface, indicating that the adhesive strength had exceeded the tensile strength of the lightweight brick. Regression analysis showed a very strong relationship between compressive force and bond strength, indicating that applied pressure was the dominant factor in bond effectiveness.